Pembangunan Berbasis Waterfront dan Transformasi Konflik di Bantaran Sungai: Sebuah Pemikiran Awal - Cahyo Seftyono (Jurnal Ilmu Sosial dan Ilmu Politik, 2012)
Water resources development at this time led to the front view policy known as waterfront term. This policy is to make water resources as the main area for regional development. The concept of ‘front view’ was developed originally to give understanding to people of the water resources as not only functional but also interesting to look at. On the other side, front view-based development has become the means of developing active interaction among people aroung the site.With regard to the construction of waterfront along the river, the social interaction of community members has become more meaningful, because apparently this is the cause of the unity of the community in the development of their area. As the most communities along the river are lower middle class people who are prone to conflict, this idea of front view-based river bank construction has united the people on one side of the river with another.